Makna motif sirih pada tradisi Melayu di Sumatra Utara - Siregar, Nayla Salsabila Br; Irawan, Indra; Insani , Husnil (Program Studi Akuntansi IKOPIN, 2025)
The betel leaf motif is an important symbol in Malay culture, particularly in North Sumatra. Betel leaf is not only known as a plant used in everyday life, but also holds profound philosophical significance in social and cultural contexts. This article examines the symbolic meaning of the betel leaf motif in North Sumatran Malay tradition and its relationship to the aesthetic, ethical, and spiritual values of the Malay community. Through cultural analysis, it is discovered that the betel leaf motif reflects politeness, honor, and harmony, which are fundamental to Malay life.